OFR-125-78 Noise Control Of An Underground Load-Haul-Dump Machine - Geoffrey C. Huggins (The National Institute for Occupational Safety and Health (NIOSH), 1977)
Diagnostic: tests were performed on a production ST-5A Load-Haul-Dump machine manufactured by Wagner Mining Machinery Company to evaluate and rank order noise sources. The diagnostic evaluation indicated that the major noise sources were the transmission, the engine, and the cooling fan. This phase was followed by implementation of recommended noise control treatments, which included vibration isolation of the transmission, a transmission enclosure, an engine enclosure, and modifications of the inlet to the cooling fan. The final step in the program was an underground operational period which began on 31 August 1976 at the National Gypsum Mine in Shoals, Indiana. The noise control treatments successfully reduced the LHD operator noise exposure by 7 dB(A), thus increasing its allowable operation time by a factor of 2.7. Actual measurements made underground using noise dosimeters have indicated that, during, a typical shift, the noise control treatments have reduced the fractional exposure to an allowable level. The report discusses the mechanical aspects of the LHD, its noise sources, the treatments applied, the final levels achieved, and field experience with the noise-controlled machine.